The Global Least-cost user-friendly CLEWs Open-Source Exploratory model. (September 2021) - Beltramo, Agnese; Ramos, Eunice Pereira; Taliotis, Constantinos; Howells, Mark; Usher, Will
Abstract: Integrated Assessment Models (IAMs) are important tools to analyse cross-sectoral interdependencies and the use of global resources. Most current tools are highly detailed and require expert knowledge and proprietary software to generate scenarios and analyse their insights. In this paper, the complementary Global Least-cost User-friendly CLEWs Open-Source Exploratory (GLUCOSE) model is presented as a highly-aggregated global IAM, open and accessible from source to solver and using the OSeMOSYS tool and the CLEWs framework. The model enables the exploration of policy measures on the future development of the integrated resource system. Thanks to its relatively simple structure, it requires low computational resources allowing for the generation of a large number of scenarios or to quickly conduct preliminary investigations. GLUCOSE is targeted towards education and training purposes by a range of interested parties, from students to stakeholders and decision-makers, to explore possible future pathways towards the sustainable management of global resources. Highlights: GLUCOSE is a global, highly aggregated, CLEWs-based IAM, open from source to solver. The model is designed for education and communication purposes. GLUCOSE shows how combined cross-sectoral policies are beneficial for all resources. The paper highlights the lack of globally aggregated, transparent, reliable and consistent data.